' … or els to bridewell': The Different Roles Sustained by Coventry's House of Correction, 1580-1680. (2nd January 2022) - Chester, John
ABSTRACT: This article argues that Coventry's house of correction did not follow the general tendency for such institutions by becoming a mere lock-up, but instead formed a long-lasting part of the corporation's attempts to strengthen the city's social fabric. Despite several crises as successive masters fell out of favour, it remained one of a small minority of urban bridewells able to set prisoners to work, whilst also developing a range of relief roles: providing work for the destitute, temporary refuge for vulnerable children and adults, and later pre-apprenticeship training for boys from the hospital school. The size of its premises, the corporation's use of alternative punishments to spread the penal load, and the rigorous measures taken to exclude strangers, contributed to the bridewell's ability to maintain its range of provision for the city.